(untitled) (diségno, 2023)
The third national conference of Italian doctorates in architecture, planning, design, arts and fashion (figs. 1, 2) –promoted by the doctoral school of the Università Iuav di Venezia– aims to provide a complete picture of the status and prospects of doctorates of the scientific areas involved, analyzing what are and what may be the first openings with respect to today’s surrounding territorial and productive reality. [read more]